Daptomycin versus linezolid for the treatment of vancomycin-resistant enterococcal bacteraemia: implications of daptomycin dose. (October 2016) - Chuang, Y.-C.; Lin, H.-Y.; Chen, P.-Y.; Lin, C.-Y.; Wang, J.-T.; Chang, S.-C.
Abstract: Treatment options for vancomycin-resistant enterococci (VRE) bloodstream infection are limited. Studies comparing daptomycin or linezolid in treating VRE bloodstream infection have conflicting results and suggest daptomycin underdosing. The responses to different daptomycin doses have not been studied. We conducted a multicentre prospective cohort study to compare linezolid and daptomycin (≥6 mg/kg) for the treatment of VRE bloodstream infection. The primary outcome was 14-day mortality. We used multivariate logistic regression analysis for outcome analysis and a generalized additive model for dose-dependent response estimation. Two hundred twelve patients were included (daptomycin, n = 141; linezolid, n = 71). All-cause 14-day mortality was higher in the daptomycin group (36.9% vs. 21.1%; p 0.03). After adjusting for confounders in logistic regression, mortality was lower in the linezolid group (adjusted odds ratio (aOR), 0.45; 95% confidence interval (CI), 0.21–0.96; p 0.04). The generalized additive model showed that higher-dose daptomycin (≥9 mg/kg) was associated with better survival than lower-dose daptomycin (6–9 mg/kg). Logistic regression showed that linezolid (aOR, 0.36; 95% CI, 0.17–0.79; p 0.01) and higher-dose daptomycin (aOR, 0.26; 95% CI, 0.09–0.74; p 0.01) independently predicted lower mortality compared to lower-dose daptomycin. Linezolid was not superior to higher-dose daptomycin in terms of mortality (aOR, 1.40; 95% CI, 0.45–4.37; p 0.57). Higher-dose daptomycin had lower mortality than lower-dose daptomycin. Despite higher mortality for lower-dose daptomycin than linezolid, linezolid conferred no survival benefit compared to higher-dose daptomycin. Our findings suggest that the recommended daptomycin dose is suboptimal for treating VRE bacteraemia.